PENGEMBANGAN LAGU RELIGI BERBASIS WORDWALL UNTUK PEMBELAJARAN KARAKTER SISWA KELAS 1 SDN 3 CIBEUREUM - Dea Siti Wahdiati; Nunu Nurfirdaus; Dudung Abdu Salam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a learning medium in the form of religious songs based on the Wordwall platform for character education in Pancasila Education, with the goal of instilling character values in first-grade students at SDN 3 Cibeureum. The research employed a Research and Development (R&D) approach, using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Observations and questionnaires revealed that first-grade students face character-related issues such as discipline, peace-loving attitudes, and social awareness. Initial data showed that the average character assessment score was 59.7%, categorized as "fair." Meanwhile, students’ interest in religious songs was categorized as "very high" at 97.7%, with dominant learning styles being visual (42.48%) and auditory (36.60%). The learning media were developed by composing song lyrics that align with character values, integrating musical instruments, visual support, and publishing the content via the Wordwall platform. Expert validation results indicated the media were rated as "highly feasible," with scores from media experts (96%), content experts (96%), and technology experts (95.78%). The implementation of the media in the learning process received very positive responses from both students (95.55%) and teachers (96.92%). The findings indicate that the religious song-based Wordwall media are highly feasible, effective, and engaging for supporting the development of discipline, peace-loving attitudes, and social care among first-grade elementary school students.